Transformasi Digital Banking: Manfaat dan Risiko Transaksi Online Modern (Internet Banking dan Mobile Banking) - Putri Ayu Lestari; Muhammad Iqbal Fasa (Universitas Muhammadiyah Mataram, 2025)
Abstract: This research examines digital transformation in the banking sector, focusing on the benefits and risks of Internet Banking and Mobile Banking services. In the era of information technology advancement, electronic banking (E-Banking) has become an essential component in financial institutions' innovation strategies to meet customer needs for fast, easy, and secure services. Through a qualitative approach based on literature studies, this research analyzes how digital banking services provide various benefits for customers, such as time and place flexibility, cost and time efficiency, and ease of access. However, the adoption of digital banking technology also presents several security risks that need to be considered, including threats of card skimming, social engineering, phishing, malware, and fake websites. Additional risks in Mobile Banking include aspects of privacy, information security, learning time, application performance, costs, and social risks. The research results emphasize the importance of balance between perceived customer benefits and effective risk mitigation for the successful implementation of digital banking services. Banks must strengthen security systems and provide education to customers regarding digital security practices, to build trust and encourage sustainable use of Internet Banking and Mobile Banking.Abstrak: Penelitian ini mengkaji transformasi digital pada sektor perbankan, dengan fokus pada manfaat dan risiko dari layanan Internet Banking dan Mobile Banking. Di era kemajuan teknologi informasi, perbankan elektronik (E-Banking) telah menjadi komponen penting dalam strategi inovasi lembaga keuangan untuk memenuhi kebutuhan nasabah akan layanan yang cepat, mudah, dan aman. Melalui pendekatan kualitatif berbasis studi literatur, penelitian ini menganalisis bagaimana layanan digital perbankan memberikan berbagai keuntungan bagi nasabah, seperti fleksibilitas waktu dan tempat, efisiensi biaya dan waktu, serta kemudahan akses. Namun, adopsi teknologi perbankan digital juga menghadirkan beberapa risiko keamanan yang perlu diwaspadai, termasuk ancaman card skimming, social engineering, phishing, malware, dan situs palsu. Risiko tambahan pada Mobile Banking mencakup aspek privasi, keamanan informasi, waktu pembelajaran, kinerja aplikasi, biaya, dan risiko sosial. Hasil penelitian menekankan pentingnya keseimbangan antara manfaat yang dirasakan nasabah dan mitigasi risiko yang efektif untuk keberhasilan implementasi layanan perbankan digital. Bank harus memperkuat sistem keamanan dan memberikan edukasi kepada nasabah mengenai praktik keamanan digital, guna membangun kepercayaan dan mendorong penggunaan berkelanjutan Internet Banking dan Mobile Banking.